STRENGTH AND DUCTILITY BEHAVIOR OF HIGH-STRENGTH CONCRETE COLUMNS CONFINED BY HIGH-STRENGTH STEEL - DJAUHARI (NIM 35004012); Tim Pembimbing: Ir. Iswandi Imran, MASc., Ph.D., Dr.Ir.Herlien D. , ZULFIKAR
This dissertation was conducted to study the behavior of high-strength concrete columns confined by high-strength steel subjected to concentric and eccentric monotonic axial compression loading. The study were based on critical assessment and synthesis of available data from the experimental results. Test parameters evaluated included volumetric ratio, spacing, type, and yield-strength of confining reinforcement and eccentricity of applied load position. The test specimens included 18 circular concentric and 10 square eccentric columns. The circular columns have diameter of 110 mm and height of 550 mm. The cross sections area of eccentric column is 120 mm x 120 mm and the height is 600 mm. The circular columns were confined by 6 mm diameter of spiral or hoop confinements, while the square columns confined by 6 mm diameter of ties. The confining reinforcement is made of high-strength wire rod steel. The results showed that the higher the strength and the volumetric ratio of confining reinforcement, the higher the resulting peak strength, confining stress, confinement effectiveness and ductility of high-strength concrete columns. The narrower pitch of confining reinforcement produced the same effect. Spiral confinement exhibited better performance than the hoop type. Based on this study, some recommendations are proposed. These are: 1. the maximum pitch of confining reinforcement is 10 times the diameter of confining reinforcement, 2. proposed nomogram for predicting relationship between concrete strength and yield-strength of confining reinforcement, 3. proposed procedure for design of high-strength spiral reinforcement for compression member, 4. the proposed the equivalent rectangular stress block parameters derived from this study for high-strength concrete columns confined by high-strength steel.